Electrochromic properties of multi-layer WO3 / TiO2 films made by electrochemical deposition - Thao, Tran Thi; Ninh, Dang Hai; Quyen, Nguyen Minh; Long, Pham Duy; Dinh, Nguyen Nang (VNU Journal of Science: Mathematics - Physics, 2011)
Abstract: Multilayer thin films of WO 3 /TiO 2 /FTO containning inorganic heterojunctions such as TiO 2 /FTO and WO 3 /TiO 2 were prepared by electro-chemical deposition technique. From the cyclic voltammetry (CV) characteristics one can suggest that in the WO 3 /TiO 2 /FTO multi-layer films there is also W-doped TiO 2 structure, creating multi-heterojunctions of  WO 3 , TiO 2 :W, TiO 2 and F-doped SnO 2 . Combining CV, time-current characteristic, in-situ transmittance spectra, the electrochromic performance of WO 3 /TiO 2 /FTO was revealed. It is seen that the multi-layer electrochromic devices exhibited much larger electrochromic efficiency and faster response time than that of a standard single layer electrochromic device. Keywords: Electrochromic device (ECD), Electrochemical deposition, in-situ transmittance spectra, ion insertion / extraction, heterojunction.